2014
DOI: 10.2807/1560-7917.es2014.19.45.20959
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of seasonal influenza vaccination during pregnancy in preventing influenza infection in infants, England, 2013/14

Abstract: Binary file ES_Abstracts_Final_ECDC.txt matches

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 11 publications
3
47
0
1
Order By: Relevance
“…For subjects younger than 6 months, infant protection from influenza can be assured by maternal vaccination. 67,68 Administration of influenza vaccine is recommended by several health authorities for pregnant women at-risk because suffering from a severe chronic underlying disease. Moreover, considering that influenza can be a disease significantly more severe in pregnant women than in the general population leading in many cases to hospitalization and rarely to death, many health authorities suggest influenza vaccine also to otherwise healthy pregnant women.…”
Section: Influenza Vaccine Administration To Pregnant Womenmentioning
confidence: 99%
“…For subjects younger than 6 months, infant protection from influenza can be assured by maternal vaccination. 67,68 Administration of influenza vaccine is recommended by several health authorities for pregnant women at-risk because suffering from a severe chronic underlying disease. Moreover, considering that influenza can be a disease significantly more severe in pregnant women than in the general population leading in many cases to hospitalization and rarely to death, many health authorities suggest influenza vaccine also to otherwise healthy pregnant women.…”
Section: Influenza Vaccine Administration To Pregnant Womenmentioning
confidence: 99%
“…In the US, effectiveness of the vaccine given to pregnant women was 45-92% in preventing seasonal influenza-related hospitalizations in infants aged <6 months [55,56]. In England during the 2013-2014 influenza season, vaccination prevented 71% of influenza infections in infants aged <6 months and 64% of infant hospitalizations due to influenza [57]. Results from a randomized controlled trial in Bangladesh provided a proof of concept that maternal vaccination could reduce infant influenza disease in developing countries, with 36% efficacy against febrile respiratory illness in mothers and 29% in infants and 63% efficacy against confirmed influenza illness in infants, compared to the 23-valent pneumococcal polysaccharide vaccine [58].…”
Section: Influenzamentioning
confidence: 99%
“…[73][74][75] Vaccine effectiveness in the studies that used a laboratory confirmed end point ranged from 48% to 91.5%. 73,74 These demonstrate the importance of the vaccine in reducing severe disease and hospitalization in children too young to be vaccinated.…”
Section: Maternal Influenza Immunization For Infantsmentioning
confidence: 99%